Effects of Allegations Regarding the Use of Antibiotics and Hormones in Diets on Consumer Perceptions, Attitudes and Behaviors towards Broiler Meat Consumption - Kerem Karasu; Ergin Ozturk (Turkish Journal of Agriculture: Food Science and Technology)
This research has been carried out to determine the effects of the current misinformation (hormone, antibiotic, feed additives and growth of broiler chickens in a short period) on consumers' view of the poultry meat sector. The survey was conducted in Istanbul province which better reflects the socio-cultural and socio-economic structure of Turkey, and with different demographic structure of 384 people face to face survey method was applied. Questions were asked to determine whether antibiotics and hormones were used in the diet of broiler chickens, and consumers' perceptions, attitudes and behaviors about the reliability of chicken meat. According to the results of the study, 73.4% of the consumers stated that they did not know about the contents of broiler diets. A big majority of the consumers (88.3%) stated that they think hormone is used and 84.6% think antibiotics is used in the feeding of broiler chickens. 78.4% of consumers surveyed stated that they think that broiler chickens are not fed with healthy feed. Also, 70.6% of consumers stated that rapid growth was due to use of antibiotics and hormones. Although the use of hormones and antibiotics as growth promoters in poultry feeds is prohibited, consumers think that they are used as additives and broiler meat is not safe food. According to these results, creating a positive effect on the purchasing decisions of the consumers is important for the sustainability and future of the sector.